Correlation of petiole sap nitrate-nitrogen concentration measured by ion selective electrode, leaf tissue nitrogen concentration, and tomato yield in Florida. (14th October 2016) - Carson, Luther; Ozores-Hampton, Monica; Morgan, Kelly
ABSTRACT: The effectiveness of measuring petiole sap nitrate-nitrogen concentration (PSNC) using ion selective electrode (ISE) has been scrutinized due to claims that PSNC poorly predicts leaf tissue nitrogen concentration (LTNC) or crop yield. This study evaluated the relationship among PSNC, LTNC, and marketable yield of tomato ( Solanum lycopersicum L.). Two tomato trials were conducted using seepage irrigation and controlled-release fertilizer (CRF) in fall 2011 and 2012. At 15 days intervals, six most recently mature leaves were collected to measure PSNC and LTNC. PSNC and LTNC declined throughout the growing seasons, but PSNC was affected by weather. PSNC and LTNC were correlated (P = 0.0001, r = 0.38), though not meaningfully. PSNC and LTNC correlated negatively and positively with crop yield in most correlations, respectively. Correlations of CRFs and soluble fertilizers (SFs) separately, did not improve relationships. Measuring LTNC may be a more reliable nutrient management tool compared to PSNC measured using an ISE.